2020
DOI: 10.1007/s41742-020-00245-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Composite Sorbent Coated with Siderite Nanoparticles and its Application for Remediation of Water Contaminated with Congo Red Dye

Abstract: Re-use of the byproduct wastes resulting from different municipal and industrial activities in the reclamation of contaminated water is real application for green projects and sustainability concepts. In this direction, the synthesis of composite sorbent from the mixing of waterworks and sewage sludge coated with new nanoparticles named "siderite" (WSSS) is the novelty of this study. These particles can be precipitated from the iron(II) nitrate using waterworks sludge as alkaline agent and source of carbonate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…As an alternative method, adsorption process in the treatment of dye-contaminated wastewaters can be used due to its simplicity, high efficiency, low costs, ease and flexibility of operation, easy desorption. In recent years, lots of novel adsorbents such as functionalized multiwalled carbon nanotubes [ 25 ], graphene oxide/clay nanocomposite [ 26 ], doped metal oxide [ 27 ] or derived from industrial solid wastes [ 28 ], agricultural solid wastes [ 29 , 30 ], biopolymers and their composites [ 31 , 32 , 33 ], sewage sludge [ 34 ], fly ash [ 35 ] have been reported in the literature. Although all the materials seem to be very promising, activated carbon is still the most common adsorbent for wastewaters treatment of in industrial plants contaminated with dyes.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative method, adsorption process in the treatment of dye-contaminated wastewaters can be used due to its simplicity, high efficiency, low costs, ease and flexibility of operation, easy desorption. In recent years, lots of novel adsorbents such as functionalized multiwalled carbon nanotubes [ 25 ], graphene oxide/clay nanocomposite [ 26 ], doped metal oxide [ 27 ] or derived from industrial solid wastes [ 28 ], agricultural solid wastes [ 29 , 30 ], biopolymers and their composites [ 31 , 32 , 33 ], sewage sludge [ 34 ], fly ash [ 35 ] have been reported in the literature. Although all the materials seem to be very promising, activated carbon is still the most common adsorbent for wastewaters treatment of in industrial plants contaminated with dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Stepwise approach must be applied to represent the adsorption and precipitation mechanisms that resulted from interaction of aqueous solution of heavy metal and CKD as described previously. is approach is required to formulate each mechanism alone, and then the final results are collected together as follows [24,[27][28][29]:…”
Section: Derivation Of Kinetic Model For Ckd-metal Ions Interactionmentioning
confidence: 99%
“…So, there is another mechanism rather than the pure adsorption which governed the treatment process which known as "pure precipitation." In addition, the last group of these studies is considered the treatment process as just interaction between contaminant and reactive material regardless which mechanism governed the removal of contaminant or what the contribution and adsorption when occurred together [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Kurniawan et al (2005) reported that most solid adsorbents such as industrial wastes, zeolites, biomass materials, agricultural wastes, and polymeric materials might be used for the reduction of inorganic effluent mine water. Among various water and wastewater treatment technologies, process techniques including physicochemical treatment techniques for wastewater (Solimana and Moustafa, 2020), electrodialytic process by various fly ashes for treating heavy metals (Pedersen et al, 2003), photocatalytic (Skubal et al, 2002), coagulationflocculation process (Hakizimana et al, 2017;Emad et al, 2020), water and wastewater treatment by flotation (George et al, 2018), biological filtration process (Shuokr et al, 2016), ion exchange process for wastewater treatment (Nirali et al 2016), biodegradable processes of sewage by an aerobic and anaerobic process (Anijiofor et al, 2017;, water and wastewater purification using photochemical Advanced Oxidation Processes (Marta and Natalia, 2010), solvent extraction and adsorption for wastewater effluent (Aswathy et al 2016), water treatment and purification by adsorption processes (Adrián et al 2017;Alshammari et al, 2020), electrolytic treatment of wastewater (Vinod Kumar, 2017;Jannatul et al, 2020), activated microbial sludge treatment for wastewater (Yongkui, 2020), chemical reduction of chlorinated organic compounds (Rodrigues et al, 2020), a catalyzed by laccase in aqueous solution (Asadgol et al, 2014); green synthesis iron oxide nanoparticles (Ehrampoush et al, 2015); Magnetic heterogeneous catalytic ozonation (Shahamat et al 2014); ultrasound waves and ultraviolet irradiation; carbon nanotubes: kinetic and equilibrium studie (Mahvi et al, 2009); magnetic adsorption separation process (Dehghani et al 2015); electro-coagulation process using iron and aluminum electrodes (Azari et al 2017).…”
Section: Introductionmentioning
confidence: 99%